The influence of intellectual capital on financial performance with firm size as a moderating variable - Agita Mellara Sari; Erni Masdupi (Universitas Negeri Padang, 2021)
This study aims to analyze the effect of intellectual capital on financial performance in manufacturing companies listed on the Stock Exchange with firm size as a moderating variable. The research population is all manufacturing companies listed on the IDX for the 2014-2018 period. The sample in this study was determined by purposive sampling technique. The analytical method used is the Moderated Regression Analysis (MRA) model using the SPSS 25 data processing application. The results of this study conclude that VAIC and VACA have no significant effect on financial performance. While VAHU and STVA have a significant effect on financial performance. Furthermore, firm size has no significant effect in moderating the relationship between VAIC and financial performance and the relationship between VACA and financial performance. However, firm size has a significant effect in moderating the relationship between VAHU financial performance and the relationship between STVA and financial performance.